Use of cellulose microfibers from olive pomace to reinforce green composites for sustainable packaging applications - Amara, Cyrine; El Mahdi, Ayoub; Akman, Perihan Kubra; Medimagh, Raouf; Tornuk, Fatih; Khwaldia, Khaoula (WILEY, 2023)
To valorize abundant, unexploited, and low-cost agro-industrial by-products, olive pomace is proposed as a sustainable and renewable raw material for cellulose microfibers (CMFs) production. In this study, CMFs were extracted from olive pomace using alkaline and bleaching treatments and characterized in terms of morphological, structural, and thermal properties. Afterward, the reinforcing capability of microfibers was examined using carboxymethyl cellulose (CMC) as a polymer matrix by the solvent casting process. The effects of CMF loading (1%, 3%, 5%, and 10%) on the composites' mechanical, physical, morphological, and thermal properties were assessed. CMF incorporation led to a decrease in moisture content (MC), water solubility (WS), and water vapor permeability (WVP) and an increase in tensile strength (TS), stiffness and transparency values, and thermal stability of CMC films. Increasing CMF content to 5%, increased the TS and elasticity modulus by 54% and 79%, respectively, and reduced the WVP and light transmissivity at 280 nm, by 22% and 47%, respectively. The highest water, moisture, light barrier, and mechanical properties of composites were reached at 5% CMFs.
Keywords: cellulose microfibers; composite films; olive pomace; packaging; MICROFIBRILLATED CELLULOSE; CARBOXYMETHYL CELLULOSE; ALPHA FIBERS; NANOCRYSTALS; EXTRACTION; STARCH; CHITOSAN; BARRIER; Food Science & Technology